Stress level and preliminary assessment of Burnout syndrome in ICU nurses at COVID-19 - Case study research (Research, Society and Development, 2022)
Objective: Analyze the level of stress and preliminary signs of Burnout Syndrome in nurses working in Intensive Care Units (ICUs) of COVID-19 and, in other ICUs, in the context of the pandemic. Methodology: Cross-sectional, descriptive study with a quantitative analytical approach, carried out from February to May 2021, with nurses from the ICUs of a Teaching Hospital in the interior of the state of São Paulo. We applied a structured form through Google Forms, associated with the Health Professional Stress Questionnaire from Gomes & Teixeira and the JBEILI Questionnaire, inspired by the Maslach Burnout Inventory – MBI (Chafic Jbeili). For statistical analyses, the significance level of p ≤ 0.050 was adopted, and correlation analysis, normality test, Wilcoxon statistical tests, Mann-Whitney U, and Spearman correlation tests were performed. Results: The study population consisted of 61 nurses. Of these, 38 work in the COVID-19 ICUs and 23 in the other ICUs. There were no statistically significant differences regarding the level of stress and the preliminary analysis of Burnout between the two groups. As for the level of global stress identified in the QSPS, the classification of high stress (34%) predominated, followed by high stress (24%) and, concerning the preliminary analysis of Burnout, 82% of the total population presented the Burnout Syndrome, predominating the classification "Initial Stage of Burnout." Conclusion: The results score global stress levels from “quite” to “high” and predominance of the initial and installation phase of Burnout syndrome in nurses from COVID-19 ICUs and other ICUs. The results point to global stress levels ranging from “quite” to “high” stress, with Burnout predominating in nurses in the COVID-19 ICUs and other ICUs in the initial phase and beginning of the syndrome's onset.